Graphene Oxide Catalyzed Synthesis of Fused Chromeno Spiro Pyrrolidine Oxindoles via Tandem Decarboxylation and 1,3-Dipolar Cycloaddition - Singh, Vipin; Lakshmi, Shanta Raj; Chowhan, L. Raju (Frontiers in Chemistry, 2022)
A short and efficient multicomponent sequence for the synthesis of fused novel polyheterocyclic chromeno spiro pyrrolidine oxindoles via 1,3 dipolar cycloaddition reaction mediated by reactive azomethine ylides, catalyzed by the Graphene Oxide (GO) is reported herein. This approach was utilized for synthesizing fused polyheterocyclic spiro- pyrrolothiazole and spiro-pyrrole oxindoles with yields ranging from good to excellent. A heterogeneous GO catalyst was utilized with an ultra-low catalytic loading of 0.05 wt% could proficiently catalyze the reaction without the formation of any side products. The methodology is green in nature and the products were isolated by simple filtration without the use of any chromatographic techniques.